Psychophysiological effects of yoga on stress in college students - Mahesh Narain Tripathi; Sony Kumari; Tikhe Sham Ganpat (Wolters Kluwer Medknow Publications, 2018)
College students are vulnerable to a critical period in developmental maturation, facing rigorous academic work, and learning how to function independently. Physical activities such as running and bicycling have been shown to improve mood and relieve stress. However, college students often have low levels of physical activity. Yoga is an ancient physical and mental activity that affects mood and stress. However, studies examining the psychophysiological effects of yoga are rare in peer-reviewed journals. The aim of this study is to establish preliminary evidence for the psychophysiological effects of yoga on stress in young-adult college students. The present study suggests that yoga has positive effects on a psychophysiological level that leads to decreased levels of stress in college student. Further research is needed to examine the extent to which different types of yogic practices address the needs of different college subpopulations (e.g., overweight, sedentary, and smokers).